(untitled) - Higgs, Edward (New York, N.Y., 2004)
There has been an enormous rise in the central state's collection of information on individuals since the sixteenth century. Historians have mined this rich seam for their own ends, but--until now--analysis of the significance of this information gathering has been mainly left to sociologists. Raising questions with immense contemporary relevance, Edward Higgs examines how and why the central state has become ever more involved in the collection and manipulation of personal information for both benign and repressive ends.
Keywords: Public records,Government information,Public records,Government information; History,History,History,History; Wales,Wales,England,England